Calculations of S values and effective dose for the radioiodine carrier and surrounding individuals based on Chinese hybrid reference phantoms using the Monte Carlo technique. (7th September 2015) - Geng, Changran; Tang, Xiaobin; Qian, Wei; Guan, Fada; Johns, Jesse; Yu, Haiyan; Gong, Chunhui; Shu, Diyun; Chen, Da
Abstract: The S values for the thyroid as the radioiodine source organ to other target organs were investigated using Chinese hybrid reference phantoms and the Monte Carlo code MCNP5. Two radioiodine isotopes 125 I and 131 I uniformly distributed in the thyroid were investigated separately. We compared our S values for 131 I in Chinese phantoms with previous studies using other types of phantoms: Oak Ridge National Laboratory (ORNL) stylized phantoms, International Commission on Radiological Protection (ICRP) voxel phantoms, and University of Florida (UF) phantoms. Our results are much closer to the UF phantoms. For each specific target organ, the S value for 131 I is larger than for 125 I in both male and female phantoms. In addition, the S values and effective dose to surrounding face-to-face exposed individuals, including different genders and ages (10- and 15-year-old juniors, and adults) from an adult male radioiodine carrier were also investigated. The target organ S values and effective dose for surrounding individuals obey the inverse square law with the distance between source and target phantoms. The obtained effective dose data in Chinese phantoms are comparable to the results in a previous study using the UF phantoms. The data generated in this study can serve as the reference to make recommendations for radiation protection of the Chinese patients or nuclear workers.